2013
DOI: 10.1021/jf403067c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chromium Species in Dietary Supplements Using Speciated Isotope Dilution Mass Spectrometry with Mass Balance

Abstract: In order to determine the health impact of chromium in dietary supplements, the Cr(III) and Cr(VI) must be independently measured and verified with mass balance (sum of both species equaling independent measurements of total chromium), as both may be present in finished products. Because Cr(III) is stable in acidic conditions and Cr(VI) in alkaline conditions, interconversions between species may occur in complex matrices and during analytical extraction, increasing the difficulty of quantification. A study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…The potential monitoring enforcement should therefore encompass not only microalgal-based formulations but all food supplements. Previous studies have shown that some food supplements may be contaminated with the hexavalent form of Cr (Martone et al 2013) which is recognized as a human carcinogen (Sun et al 2015). Thus, it remains important to screen microalgal products to exclude such contamination and, as shown in the present study, none of the Spirulina and Chlorella products contained detectable levels of the Cr (VI) form.…”
Section: Discussionsupporting
confidence: 51%
“…The potential monitoring enforcement should therefore encompass not only microalgal-based formulations but all food supplements. Previous studies have shown that some food supplements may be contaminated with the hexavalent form of Cr (Martone et al 2013) which is recognized as a human carcinogen (Sun et al 2015). Thus, it remains important to screen microalgal products to exclude such contamination and, as shown in the present study, none of the Spirulina and Chlorella products contained detectable levels of the Cr (VI) form.…”
Section: Discussionsupporting
confidence: 51%
“…None of analyzed products contained detectable levels of the Cr(VI) form known to act as a carcinogen (Sun et al 2015). This is a very important finding if one considers a previous disquieting report of Cr(VI) constituting up to a 16% share in the total Cr quota in some FS available on the U.S. market (Martone et al 2013).…”
Section: Discussionmentioning
confidence: 81%
“…Despite the recognition of this problem, clay-based products are consumed by pregnant women and others in many parts of the world. In order to separately measure concentrations of Cr III and Cr VI avoiding any inter-species conversion, Martone et al 144 used the EPA method 3060A to extract Cr VI followed by EPA method 3052 to separate Cr III from the residue. Christopher et al 18 used ID-ICP-MS to determine the concentration of Cd in the SRM 3280 Multivitamin/Multielement Tablets.…”
Section: 49mentioning
confidence: 99%